Effects of functional level on balance in children with Duchenne Muscular Dystrophy. (July 2017) - Alkan, Halil; Mutlu, Akmer; Fırat, Tüzün; Bulut, Numan; Karaduman, Aynur Ayşe; Yılmaz, Öznur Tunca
Abstract: Introduction: This study was planned to compare the static and dynamic balance in children with Duchenne Muscular Dystrophy (DMD) at different functional levels with each other and with healthy peers. Material and methods: Sixty nine children between the ages of 6 and 11 were included in this study where 52 of them were diagnosed with DMD in Level I (18 patients), Level II (17 patients), and Level III (17 patients) according to Brooke Functional Classification Scale and 17 of them healthy peers were included. In order to assess static and dynamic balance pediatric functional reach test (PFRT) and timed up and go test (TUGT) were used. Results: When compared in terms of the TUGT, differences were found between all groups, i.e. Level 1 and 2, Level 2 and 3, Level 1 and 3, Healthy peers and Level 1, Healthy peers and Level 2, and Healthy peers and Level 3 (p < 0.0083). When compared in terms of the PFRT in the standing positions, there was difference between level 3 and healthy peers (p < 0.0083), but not between the other groups. Conclusions: We found poor functional level in DMD to affect the dynamic and static balance parameters in this study. The dynamic balance of a child with DMD at Level 3 is decreased to a third of a healthy peer. Highlights: The dynamic balance decreases significantly with the decrease of functional level in children with DMD. The dynamic balance of a child with DMD at Level 3 is equivalent to one third of a healthy peer. The static balance in sitting does not change with the decrease of functionality in children with DMD. Static balance in the standing position decreases in children with DMD compared to the healthy peers.